2005
DOI: 10.2214/ajr.04.0466
|View full text |Cite
|
Sign up to set email alerts
|

Peroral CT Enterography with Lactulose Solution: Preliminary Observations

Abstract: Peroral CT enterography performed with lactulose solution is a simple and noninvasive method of evaluating the small bowel by obtaining good distention. It can also be used at routine abdominal examinations as a negative contrast agent instead of iodinated oral contrast medium, especially for CT angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…The results of our study are in accordance with previous investigators who demonstrated that bowel wall was visualized better with other neutral oral contrast agents, such as lactulose (16), mannitol (17,18), cellulose (19), methylcellulose (20), mucofalk diluted in water (Falk, Feiburg, Germany) (1, 21), and polyethylene glycol (2,22). Some of these solutions are widely used, particularly in Europe.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study are in accordance with previous investigators who demonstrated that bowel wall was visualized better with other neutral oral contrast agents, such as lactulose (16), mannitol (17,18), cellulose (19), methylcellulose (20), mucofalk diluted in water (Falk, Feiburg, Germany) (1, 21), and polyethylene glycol (2,22). Some of these solutions are widely used, particularly in Europe.…”
Section: Discussionsupporting
confidence: 92%
“…Neutral or low-density oral contrast media are a prerequisite for good-quality CT enterography [3][4][5] because they maximise contrast between the lumen and enhancing small bowel wall, facilitating assessment of mucosal thickening and wall stratification/enhancement patterns [1][2][3][4][5][6][7][8]. Water-methylcellulose solution, polyethylene glycol, commercially available low-density barium, 0.1% Volumen (Bracco, Milan, Italy) and milk are examples of neutral oral contrast agents with CT attenuation properties similar to that of water.…”
Section: Luminal Contrast and Distensionmentioning
confidence: 99%
“…For the CT enterography portion of the study, a large volume of bowel-distending negative contrast material was administered (13). A 1,250-mL volume of the solution, which comprised 1,000 mL of water and 250 mL of lactulose (670 mg/mL) (Laevolac; Fresenius-Kabi), was ingested orally over 40-50 min at a steady rate.…”
Section: F-fdg Pet/ct Enterography Scansmentioning
confidence: 99%